Radiology: Imaging Trauma Patients in a Deployed Setting. (5th September 2018) - Ritter, John; O'Brien, Seth; Rivet, Dennis; Gibb, Ian; Grimes, Jamie; Hinds, Sidney; Jessinger, Robert; May, Todd; Wirt, Michael; Shackelford, Stacy; Adam, Octavian; York, Gerald; et al.
Abstract: Medical imaging plays a critical role in the rapid diagnosis, effective triage, and management of complex poly-trauma patients. High-quality medical imaging can be accomplished successfully in a deployed or wartime setting. Due to advances in aggressive resuscitation techniques and the speed of the latest generation computed tomography scanners (64-detector and beyond), rapid trauma scans utilizing computed tomography and ultrasound imaging can routinely be performed prior to taking the patient to the operating room potentially providing the trauma team with lifesaving information. This clinical practice guideline provides an overview of the imaging modalities available in austere settings, the equipment required, and the role that each plays in triaging and diagnosis of the acutely injured poly-trauma patients.